SOFTWARE PACKAGE FOR DETERMINING CHARACTERISTICS OF TASK MANAGERS OF RECONFIGURABLE COMPUTER SYSTEMS USING PRIORITY QUEUEING NETWORKS - Martyshkin, Alexey (Revista Inclusiones, 2019)
The paper presents mathematical models of task managers with a time-sharing strategy and a space-sharing strategy for reconfigurable (including multiprocessor and distributed) systems. The mathematical models under study are based on open queueing networks, with unmatched FIFO disciplines, absolute, relative and mixed priorities. The description of the developed software package for calculating the characteristics of these classes of task managers as part of reconfigurable computer systems according to given parameters is presented. The complex is characterized by a convenient visual user interface, which simplifies the procedure for setting the parameters of the modelling object and obtaining a larger number of experimental data per unit time. The proposed set of programs allows the characteristics of the entire queueing network, as well as individual systems to calculate. A significant difference between the developed software package and existing analogues is the ability to calculate stochastic queueing networks containing systems with a limited queue length in front of the service device and priority queueing systems, as well as calculating the network using several simultaneously varying initial parameters. The software package allows the parameters of the systems M / M / n / m and M / G / 1 to calculate.